Comparative Analysis of Public Expenditure - Ramanauskas, Gediminas (Ekonomika, 2002)
It is often argued that to increase economic competitiveness the role of government in economic affairs should be scaled down, providing freedom to the market mechanism. State involvement is accused for introduction of distortions and inefficiencies in economic management and the allocation of resources. In this vein the most widely used justification for the nco-liberal policy prescriptions to the Central East European countries is the claim that the economic problems in the region are primarily due to excessive state intervention. This justification was readily accepted and quickly became the conventional wisdom because it provided a convenient scapegoat, namely misguided governments meddling too much into economic affairs. Neo-liberals suggest limiting government spending to a minimum size and limiting its role to providing the public services ensuring favorable business environment. In Section 1 of this paper I analyzed the trends of public expenditure. The analysis revealed that in XX century the role of government in advanced market economies increased dramatically. This expansion was caused largely by expenditures normally associated with the “welfare state.” Governments increased their provision of social services and income transfers for the unemployed, the sick, the elderly and the poor. In Section 2 I specified nine indicators of public expenditure and compared the values of the indicators for a sample of 30 countries divided into three groups (10 countries in each group): Central East European countries, East Asian countries and Western countries. This comparative analysis, based upon extensive statistical data, revealed that the total government expenditures as a percentage of GDP were the largest in Western countries. It may indicate that the scope of government interventionism in Western countries is the largest. The research failed to produce any evidence to support the conventional view that the governments of Central East European countries interfere extensively into economic affairs.